Service marketing, value co-creation and customer satisfaction in the airsoft industry: case of a technology-based firm - Szarucki, Marek; Menet, Gabriela (Business, Management and Economics Engineering, 2018)
The main objective of the paper is to examine whether offering a co-creation opportunity as a part of service marketing strategy influences customer value creation and satisfaction in the airsoft industry. Our study uses a case study of a technology-based firm from the airsoft industry which operates internationally. The methods employed included statistical analyses based on the data collected through a survey of the technology-based company customers (n=178). Coefficients of Spearman and Kendall were used to examine the correlations between respondents’ particulars and elements influencing customer satisfaction. The study results reveal that there are different drivers involved in the marketing strategy of value co-creation and customer satisfaction, and some of them have a stronger impact on target customers. The research contributes to the present scientific publications by adding a comprehensive analysis of users’ value co-production as part of a successful marketing strategy implementation by a technology-based firm. The study emphasizes the need for more empirically grounded support for the management of value co-creation processes incorporated in firm’s marketing strategy.